Adaptive Clinical Trials: Enhancing Efficiency and Flexibility in Clinical Research - Patel, Prakash (International Journal of Medical Research, 2024)
Adaptive clinical trials (ACTs) are innovative research designs that allow modifications based on interim data without compromising scientific integrity. This flexibility enhances resource use, patient safety, and evaluation speed. ACTs feature designs like seamless phase transitions, adaptive randomization, and sample size adjustments, making them ideal for complex areas such as personalized medicine and rare diseases. Successful implementation requires rigorous planning, robust statistics, and regulatory adherence. This CME article outlines ACT principles, design strategies, and real-world applications, addressing both their potential to improve trial efficiency and the challenges involved. It aims to empower professionals to apply ACTs in advancing medical research.